Manajemen Pembelajaran di Pondok Pesantren Al-Kasyaf dalam Upaya Peningkatan Perilaku Santri Ke Arah Religius - Revita Yanuarsari; Mustadim Wahyudi; Salma Azzahra (Jurnal Pedagogik Indonesia: Yayasan Lembaga Pendidikan dan Pelatihan Ksatria Siliwangi, 2025)
Islamic boarding schools play a strategic role in shaping the religious behavior of students through an integrated learning system that combines faith, knowledge, and morals. Amidst the challenges of moral degradation among the younger generation, effective learning management is key to instilling religious values in a sustainable manner. This study aims to analyze learning management at Al-Kasyaf Islamic Boarding School in shaping the religious behavior of students. This study uses a descriptive qualitative approach with research subjects including boarding school leaders, daily administrators, teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that learning planning is formulated through educational programs and boarding school rules based on the habit of worship and good character. Organization is carried out with a clear division of roles between caregivers, teachers, and boarding school administrators. Learning is implemented consistently through various structured religious activities, while evaluation is carried out periodically through deliberation and observation of student behavior. Overall, learning management at Al-Kasyaf Islamic Boarding School has proven to be effective insystematically and continuously shaping the religious behavior of students.